Unraveling the chemical identification and biological potential of the genus Asparagopsis: a comprehensive review - Cheong, Kit-Leong; Li, Guanghui; Wang, Min; Yang, Yufeng; Zhong, Saiyi (Frontiers in Marine Science, 2024)
The genus Asparagopsis has garnered escalating attention in the spheres of marine biology and biotechnology due to its diverse chemical composition and promising biological capabilities. This all-encompassing review is dedicated to conducting an exhaustive inquiry into the chemical identification and biological importance of Asparagopsis species. By meticulously dissecting the array of chemical compounds found in genus Asparagopsis, encompassing polysaccharides, lipids, proteins, sterols, and bromoform. We unveil their potential utility in realms such as biomedicine, biotechnology, and the conservation of the environment. Furthermore, we delve into the bioactive attributes inherent in these compounds, encompassing effects such as antioxidative, antimicrobial, and anti-inflammatory properties, as well as their conceivable role in cancer treatments. Furthermore, this review underscores the environmental pertinence of genus Asparagopsis, particularly its capacity to mitigate climate change through the generation of compounds that alleviate greenhouse gas effects. Additionally, we delve into the economic facets of this genus, spanning from its integration into food additives to its contributions in cosmetics and sustainable agriculture. This comprehensive review furnishes a multi-faceted comprehension of Asparagopsis, illuminating its chemical diversity and biological significance, thereby paving the way for further explorations into its potential contributions across a spectrum of sectors.